Antenatal corticosteroids to reduce preterm deaths in low-income settings - Althabe, Fernando (2014)
In their Comment (April issue),1 Kishwar Azad and Anthony Costello raise questions that should be answered before antenatal corticosteroid treatment is scaled up to reduce preterm deaths in low-income countries. We share their concerns about the unknown overall effect of this treatment on mortality and potential safety issues in the mother. To answer these questions, we have initiated the Antenatal Corticosteroids Trial2 to assess whether or not a multifaceted intervention to increase the use of antenatal corticosteroids reduces neonatal mortality at 28 days of age, and maternal morbidity due to infections.